Representing History, Class, and Gender in Spain and Latin America - Rocha, Carolina. author. aut Link
X, 248 p.
Keywords: This anthology explores the role of children and teenagers in Latin American and Spanish Film as protagonists, victims and witnesses of societies polarized by and still grappling with the consequences of political divisions.